Business and professional foreign language acquisition through electronic multilingual terminological dictionary - Cherednichenko, Galina; Kovalchuk, Olga (My University, 2014)
The abstract presents the Development and Use of Electronic Multilingual Terminological Dictionary
Keywords: електронний словник; ділова англійська мова; мультимедіа; электронный словарь; деловой английский язык; мультимедиа; e-dictionary; business English; multimedia; кафедра ділової іноземної мови та міжнародної комунікації